2021
DOI: 10.1364/oe.422984
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric travelling wave antennas for directional light emission

Abstract: We present a combined experimental and numerical study of the far-field emission properties of optical travelling wave antennas made from low-loss dielectric materials. The antennas considered here are composed of two simple building blocks, a director and a reflector, deposited on a glass substrate. Colloidal quantum dots placed in the feed gap between the two elements serve as internal light source. The emission profile of the antenna is mainly formed by the director while the reflector suppresses backward e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We use a dipole with dipole moment oriented perpendicular to the antenna axis, i.e. along y-axis, that ensures the strongest coupling to the antenna modes, as demonstrated in our previous work [38]. The light emission assisted by excitation of leaky and guided waves excited by the dipole emitter in the dielectric antenna is directed towards the glass substrate (depicted in red).…”
Section: Model Numerical Methods and Implementationmentioning
confidence: 99%
See 3 more Smart Citations
“…We use a dipole with dipole moment oriented perpendicular to the antenna axis, i.e. along y-axis, that ensures the strongest coupling to the antenna modes, as demonstrated in our previous work [38]. The light emission assisted by excitation of leaky and guided waves excited by the dipole emitter in the dielectric antenna is directed towards the glass substrate (depicted in red).…”
Section: Model Numerical Methods and Implementationmentioning
confidence: 99%
“…We start our study by analysing a simple antenna consisting of a dielectric reflector and a rectangular-shaped director both made of HfO 2 with refractive index n = 1.9 deposited on a SiO 2 substrate. In recent works, we have experimentally and numerically demonstrated that this kind of antenna is capable of high directivity of 29.2 in magnitude [37,38]. Aiming to further improve the directivity, we firstly identify seven vital geometric parameters influencing the optimization problem: the antenna height (H), director length (DL), director width (DW), reflector length (RL), reflector width (RW), distance of the field source from the director (DD) and the reflector (RD).…”
Section: Optimization Of the Hfo 2 Rectangular-shaped Antennamentioning
confidence: 99%
See 2 more Smart Citations
“…The primary radiating mechanism of the travelling antenna is based on a travelling wave in the form of a guiding structure. A travelling antenna is different from others because the radio waves are generated by the radio frequency current in a single direction [ 50 , 51 ]. They are non-resonant and, as such, their bandwidth is wider than their resonant antennas counterpart [ 52 ].…”
Section: Antenna Overviewmentioning
confidence: 99%